Transanal total mesorectal excision: a pure NOTES approach for selected patients - Leão, P. (2015)
Background: The concept of natural orifice transluminal endoscopic surgery (NOTES) has stimulated the development of various “incisionless” procedures. One of the most popular is the transanal approach for rectal lesions. The aims of this study were to report how we standardized NOTES technique for transanal mesorectal excision without abdominal assistance, discuss the difficulties and surgical outcomes of this technique and report its feasibility in a small group of selected patients. Methods: Three consecutive female patients underwent transanal NOTES rectal resection without transabdominal laparoscopic assistance for rectal lesions. Functional results were assessed with the Fecal Incontinence Quality of Life scale and the Wexner score. Results: The technical steps are described in details and complemented with a video. All procedures were completed without transabdominal laparoscopic help. The mesorectal plane was entirely dissected without any disruption, and distal and circumferential margins were tumor-free. No major complications were observed. Functional results show a significant impairment after surgery with improvement at 6 months to levels near those of the preoperative period. Conclusions: The performance and publication of NOTES procedures are subject to much discussion. Despite the small number of patients, this procedure appears feasible and can be accomplished maintaining fecal continence and respecting oncologic principles.